EFEKTIVITAS DISKON DAN HADIAH SEBAGAI SARANA PROMOSI PENJUALAN UNTUK MENARIK NIAT BELI KONSUMEN PADA BUMBU MAGIC LEZAT - Amir Faesol (Universitas muhammadiyah malang, 2013)
Amir FaesolPT. Gawih Jaya - WismilakE-mail: amir_faesol@ymail.comABSTRACTThis research aimed to analyse (1) the consumer attitudes to discounts and gifts,(2) whether consumerattitudes to discounts and gifts have effectiveness in influencing purchase intention, (3) whetherpurchase intentions influence on purchase decisions, (4) differences in attitudes effectiveness ofdirect influence attitudes towards buying decision (5) the direct influence of attitudes on purchasedecisions through intention. The samples were 152 respondents and selected by using purposivesampling technique. The data was collected by distributing questionnaires to consumers Lezat Magicseasoning. The primary data were consists of discount gift attitudes, purchase intentions and purchasedecisions. Partial Least Square was used as an analysis tool to answer the research objectives.The results showed that consumers preferred to have promotional gifts and they compared it withdiscounts. The discounts and gifts significantly influenced to purchase intention. Furthermore, purchaseintentions significantly influenced to purchase decisions. Moreover, it showed that the moreeffective influence of attitudes to discounts and gifts to purchase decision through intention thanwithout intention. It meant there was differences influential between attitude to discount and gifts tobuying decision with and without intention.Keywords: Attitudes to discounts and gifts, purchase intention and the purchase decision